2007
DOI: 10.1902/jop.2007.060353
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Periodontal Healing of 1‐Wall Infrabony Defects After Application of Calcium Phosphate Cement Wall Alone or in Combination With Enamel Matrix Derivative: A Pilot Study With Canine Mandibles

Abstract: CPC walls with and without EMD promoted regeneration of alveolar bone and cementum in 1-wall infrabony defects. Space and stable wound healing are believed to be crucial for periodontal regeneration in non-contained infrabony defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…The histological and histomorphometrical findings indicate that the reparative type of healing, as observed in the empty group in our experiment, is consistent with numerous published reports [1, 3, 13, 24]. Our experiment showed that even three-wall periodontal defects did not regenerate spontaneously.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The histological and histomorphometrical findings indicate that the reparative type of healing, as observed in the empty group in our experiment, is consistent with numerous published reports [1, 3, 13, 24]. Our experiment showed that even three-wall periodontal defects did not regenerate spontaneously.…”
Section: Discussionsupporting
confidence: 93%
“…Also in a dog study, empty defects showed only a reparative type of healing while EMD-treated defects demonstrated varying amounts of new cementum but hardly any regenerated bone volume [13]. Adding CaP, however, with or without EMD showed significant more cementum and bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defect creation : Periodontal defects can either be created surgically (13, 30, 31), involve ligatures around teeth (32, 33), or develop naturally (34, 35). For surgical creation, defects can be made to the same size or shape to compare test groups and controls.…”
Section: Methodsmentioning
confidence: 99%